Skull reconstruction of the late Miocene ape Rudapithecus hungaricus from Rudabánya, Hungary. Issue 138 (January 2020) - Gunz, Philipp; Kozakowski, Stephanie; Neubauer, Simon; Le Cabec, Adeline; Kullmer, Ottmar; Benazzi, Stefano; Hublin, Jean-Jacques; Begun, David R.
Abstract: We report on a computer-based reconstruction of a well-preserved ape skull from late Miocene deposits in Rudabánya, Hungary. Based on micro-computed tomographic scans of the original Rudapithecus hungaricus partial cranium RUD 200 and the associated mandible RUD 212 we realign displaced bone fragments, and reconstruct the shape of the upper and lower jaws guided by occlusal fingerprint analysis of dental wear patterns. We apply geometric morphometric methods based on several hundred landmarks and sliding semilandmarks to estimate missing data, and create multiple reconstructions of the specimen. We then compare the reconstructed overall cranial shape, as well as the volume and shape of the endocast, with extant primates. Multiple reconstructions of RUD 200 yield an average endocranial volume of 234 cc (S.D.: 9 cc; range: 221–247 cc). RUD 200 is most similar to African apes in overall cranial shape, but in a statistical analysis of endocranial shape the specimen falls closest to extant hylobatids. Our data suggest that R. hungaricus from the late Miocene in Europe displays aspects of the overall cranial geometry typical of extant African great apes, but it does not show an evolutionary reorganization of the brain evident in Pan, Gorilla, and Pongo .